Protective effect of tanshinone IIA on H2O2-induced oxidative stress injury in rat cardiomyocytes by activating Nrf2 pathway. (3rd May 2020) - Yang, Guang; Wang, Fang; Wang, Yan; Yu, Xiaojing; Yang, Shaohui; Xu, Hongxia; Xing, Jiankun
Abstract: To investigate the protective effect of tanshinone IIA on H2 O2 -induced oxidative stress injury in rat cardiomyocytes, and further to study its potential mechanisms. H9C2 cells were used to establish H2 O2 injury model. The cell viability and apoptosis were detected by CCK-8 assay and flow cytometry, respectively. ELISA was used to detect the levels of lactate dehydrogenase (LDH), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px). Moreover, the levels of malondialdehyde (MDA) and catalase (CAT) were tested by TBA and visible light methods, respectively. The Nrf2 pathway-related proteins were detected by Western blot. To validate the protective effect of tanshinone IIA on rat cardiomyocytes is worked by regulating the Nrf2 pathway, we further silenced Nrf2 and the above experiments were repeated. Tanshinone IIA could promote the proliferation, and reduce the apoptosis and ROS of rat cardiomyocytes induced by H2 O2 . Tanshinone IIA also could increase the activity of SOD, CAT, and GSH-Px, and decreased the activity of MDA and LDH. The protein expression of Nrf2, HO-1, and NQO1 was significantly up-regulated in tanshinone IIA groups, while the protein expression of Keap1 was significantly down-regulated. A further study has shown that silenced Nrf2 has completely opposite results. All those results suggested that tanshinone IIA could protect H2 O2 -induced oxidative stress injury in rat cardiomyocytes by activating Nrf2 pathway.